817 Robotic Semi-Automated Transcranial Doppler Assessment of Cerebrovascular Autoregulation in Post Concussional Syndrome: Methodological Considerations. (4th May 2021) - Khan, D Z; Placek, M M; Smielewski, P; Budohoski, K P; Anwar, F; Hutchinson, P J A; Bance, M; Czosnyka, M; Helmy, A
Abstract: Introduction: : Post-concussive syndrome (PCS) refers to a constellation of physical, cognitive, and emotional symptoms after traumatic brain injury (TBI). Despite its incidence, the underlying mechanisms are unclear. We hypothesised that impaired cerebral autoregulation (CA) is a contributor. Method: : A prospective, observational study was integrated into outpatient clinics at a tertiary neurosurgical centre. Data points included: demographics, symptoms (Post-Concussion Symptom Scale [PCSS]), neuropsychological assessment (Cambridge Neuropsychological Test Automated-Battery [CANTAB]) and cerebrovascular metrics (Mxa co-efficient and the transient hyperaemic-response ratio [THRR]) - via transcranial Doppler (TCD), plethysmography and bespoke software (ICM+). Results: : 12 participants were recruited with 2 excluded after unsuccessful cerebrovascular TCD insonation. 10 participants (5 TBI patients, 5 healthy controls) were included in the analysis (median age 26.5, male:female 7:3). Median PCSS scores were 6/126 (TBI subgroup). Median CANTAB percentiles were 78 (healthy controls) and 25 (TBI). Mxa was calculated for 90% and THRR for 50% of participants. Median study time was 127.5 minutes and feedback (n = 6) highlighted the perceived acceptability of the study. Conclusions: : This pilot study has demonstrated a feasible and reproducible assessment of PCS and CA metrics (non-invasively) in a real-world setting. By scaling this methodology, we hope to test whether CA changes are correlated with symptomatic PCS in patients post-TBI.